2019
DOI: 10.3390/nu11071555
|View full text |Cite
|
Sign up to set email alerts
|

Gastrostomy Placement and Management in Children: A Single-Center Experience

Abstract: BACKGROUND: To prevent malnutrition and food aspiration in children with chronic neuromuscular problems, enteral nutrition provided by gastrostomy is recommended. Long-term follow-up data about surgical and medical complications of PEG are available, but few papers have addressed all of the issues in the same series. METHODS: This retrospective study enrolled patients under 18 years who had a gastrostomy tube placed at our institution between 2003 and 2017. The aim is to evaluate outcomes after gastrostomy pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…When the distribution of the 130 patients in this study was analyzed, patients with neurological problems were found to comprise the largest group. This is consistent with large series published in the world 7,9,10 . Srinivasan et al 11 reported the most common indications for PEG as neurological diseases, followed by congenital heart diseases and chronic lung diseases, cleft palate, cleft lip, genetic diseases, malignancies, and metabolic diseases, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When the distribution of the 130 patients in this study was analyzed, patients with neurological problems were found to comprise the largest group. This is consistent with large series published in the world 7,9,10 . Srinivasan et al 11 reported the most common indications for PEG as neurological diseases, followed by congenital heart diseases and chronic lung diseases, cleft palate, cleft lip, genetic diseases, malignancies, and metabolic diseases, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Srinivasan et al 11 reported the most common indications for PEG as neurological diseases, followed by congenital heart diseases and chronic lung diseases, cleft palate, cleft lip, genetic diseases, malignancies, and metabolic diseases, respectively. In other studies, the most significant indications for PEG included dysphagia due to neurological disorders 10 , neuromuscular and metabolic causes, congenital heart diseases, oncological diseases, cystic fibrosis, and esophageal diseases 1,8,9,12 .…”
Section: Discussionmentioning
confidence: 99%
“…In a case series report, 84 children with neurocognitive impairment received gastrostomy due to severe dysphagia (53% of the study population), malnutrition (21.4%), risk of aspiration pneumonia (10.7%), and aversion to food (7.1%). 41 After gastrostomy placement, the number of children presenting malnutrition decreased from 33.3% to 4.4%, p < 0.0001. 41 The frequency of respiratory infection also decreased significantly, p ¼ 0.00037.…”
Section: Management General Managementmentioning
confidence: 91%
“…Based on International consensus on the diagnosis and management of dumping syndrome [ 34 ], the syndrome is subdivided into early (hyperglycaemia, gastrointestinal, and vasomotor symptoms occurring within the first hour after a meal) and late (reactive hypoglycaemia 1–3 h after a meal) forms. This pathology is a frequent complication of oesophageal and gastric surgery and was also reported in children after gastrostomy placement [ 35 ]. Dumping syndrome which occurs in non-surgical patients is classified as idiopathic.…”
Section: Discussionmentioning
confidence: 99%